ANALISIS USAHA DAN PROFITABILITAS PADA USAHA BUDIDAYA IKAN LELE STUDI KASUS KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) NGAOL JAYA DESA SUNGAI ULAK KECAMATAN NALO TANTAN KABUPATEN MERANGIN - Episar Episar; Widuri Susilawati; Evo Afrianto (JAS (Jurnal Agri Sains), 2018)
The purpose of this study was to find out the income from the fish farming business of the Ngaol Jaya Fish Cultivator Group (POKDAKAN), to determine the return cost ratio of the fish farming group Ngaol Jaya Fish Group (POKDAKAN) and to determine the value of profitability of the group fish farming business Fish Cultivator (POKDAKAN) Ngaol Jaya.The object of this research was carried out in the fish cultivation business of the Fish Cultivation Group (POKDAKAN) Ngaol Jaya in Sungai Ulak Village, Nalo Tantan District, Merangin Regency, the research method used in this research was quantitative descriptive research methods and methods of determining respondents using case study methods, analytical methods The data used are data obtained from the questionnaire then tabulated to find the total cost, acceptance, business feasibility and profitability of the Ngaol Jaya Fish Cultivator Group (POKDAKAN) business in Sungai Ulak Village, Nalo Tantan District, Merangin Regency.The results showed that the income level of fish farming business in the Fish Cultivator Group (POKDAKAN) Ngaol Jaya, Nalo Tantan District, Merangin Regency was Rp. 23,022,250.01, the business value of return cost ratio of Fish Cultivation Group (POKDAKAN) Ngaol Jaya in Sungai Ulak Village, Nalo Tantan District, Merangin Regency is 1.70 and is feasible to be continued and the profitability value of the Ngaol Jaya Fish Cultivation Group (POKDAKAN) business in Sungai Ulak Village is 70%Keywords : Effort, Profitability, Ngaol Jaya.